2019
DOI: 10.13040/ijpsr.0975-8232.10(4).1988-94
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Calotropis procera plant belongs to the Asclepiadaceae family. It is prescribed to treat bronchitis, asthma, cough, infections, cancer, ascites, intestinal worms, cutaneous diseases, eczema, leprosy and also aid to stimulate the immune system. The leaves of C. procera were investigated for their phytochemical and anti-microbial activity. Chemical screening of leaves ethanolic extract exhibited to contain active compounds like alkaloids, terpenoids, flavonoids, saponins, and reducing sugar. The antibacterial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…As shown in Table 2 and Fig. 2 the results of GC-MS analysis for leaf's methanolic extract proved the existence of one type of alkaloid compound that is colchicine by comparison with its actual retention time to the retention time of colchicine standard reference (Sigma Aldrich) at R.T(12.8) min with area percentage reached 7.1% with molecular weight 399g/mol, that was in line with the study of Naser et al 15 , that revealed the presence of colchicine compound in leaf methanolic extract of C. procera by GC-MS analysis in Iraq that, C.procera appeared to produce many bioactive compounds, such as alkaloids [21][22][23][24][25] . 3, resulted in the identification, separation, and purification of colchicine that was identified by comparison with its actual retention time to the retention time of colchicine standard reference (Sigma Aldrich)as seen in Fig.…”
Section: Gc-ms Analysis For the Leaf Methanolic Alkaloid Extractssupporting
confidence: 87%
See 2 more Smart Citations
“…As shown in Table 2 and Fig. 2 the results of GC-MS analysis for leaf's methanolic extract proved the existence of one type of alkaloid compound that is colchicine by comparison with its actual retention time to the retention time of colchicine standard reference (Sigma Aldrich) at R.T(12.8) min with area percentage reached 7.1% with molecular weight 399g/mol, that was in line with the study of Naser et al 15 , that revealed the presence of colchicine compound in leaf methanolic extract of C. procera by GC-MS analysis in Iraq that, C.procera appeared to produce many bioactive compounds, such as alkaloids [21][22][23][24][25] . 3, resulted in the identification, separation, and purification of colchicine that was identified by comparison with its actual retention time to the retention time of colchicine standard reference (Sigma Aldrich)as seen in Fig.…”
Section: Gc-ms Analysis For the Leaf Methanolic Alkaloid Extractssupporting
confidence: 87%
“…Methanol was used as a strong solvent for bioactive extraction for the leaf of C.procera. An alkaloid compounds found in large amounts in the leaf of C. procera 15 .…”
Section: Results and Discussion: Biochemical Tests For Alkaloid Compo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Octadecanoic acid is reported to be a precursor of jasmonic acid, an essential signalinducing molecule in response to biotic stress by (Coleman and Hudson 2016). Linoleic acid ethyl ester is reported to have a role as an antifungal compound (Maia et al 2022) and antibacterial (Naser et al 2019). Nonacosae compounds are reported to increase up to six times in arabidopsis plants infected with the fungus Botrytis sp.…”
Section: Metabolite Effect On Anthracnose Resistance/susceptibility P...mentioning
confidence: 99%